Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1136/vr.117.24.629
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurella species isolated from the bovine respiratory tract and their antimicrobial sensitivity patterns

Abstract: Pasteurella haemolytica biotype A, serotype 1 (P haemolytica A1) was the most commonly isolated Pasteurella species from 80 calves examined at necropsy from 40 outbreaks of respiratory disease, the majority of which were pathologically confirmed as bovine pneumonic pasteurellosis (transit fever; shipping fever). Similarly, nasopharyngeal swabs from in-contact and apparently healthy calves indicated the widespread presence of P haemolytica A1. Pasteurella multocida and other serotypes of P haemolytica A1 were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
1
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 0 publications
1
15
1
1
Order By: Relevance
“…The overall high detection rate of P. multocida (57.4%) in the nasopharynx of apparently healthy cattle is in contrast with other reports where it was found in only 0.5% of 971 (Allan et al, 1985), and 0% of 40 (Barbour et al, 1997) nasal swabs. This is probably due to the disinfection of the nostril and the use of selective medium in the present study, which minimized contamination of the samples by organisms other than Pasteurellaceae.…”
Section: Discussioncontrasting
confidence: 82%
“…The overall high detection rate of P. multocida (57.4%) in the nasopharynx of apparently healthy cattle is in contrast with other reports where it was found in only 0.5% of 971 (Allan et al, 1985), and 0% of 40 (Barbour et al, 1997) nasal swabs. This is probably due to the disinfection of the nostril and the use of selective medium in the present study, which minimized contamination of the samples by organisms other than Pasteurellaceae.…”
Section: Discussioncontrasting
confidence: 82%
“…Katoh et al [5] have shown that M. haemolytica isolates were susceptible to aminobenzylpenicillin, thiamphenicol, and enrofloxacine. Resistances to penicillin antibiotic of M. haemolytica were prevalent among cattle in North America and England [1,4,12]. This study showed that resistance to penicillin antibiotics (2 isolates) and thiamphenicol (2 isolates) was detected in Japanese isolates.…”
mentioning
confidence: 86%
“…Mannheimia haemolytica, which was previously described as Pasteurella haemolytica biotype A, is a causative pathogen of pneumonic pasteurellosis in calves and also isolated from the respiratory tract of cattle with BRDC, as well as P. multocida and Haemophilus somnus [1,10]. Although viral and bacterial vaccines have been used for preventing the individual diseases, controlling BRDC is usually difficult because BRDC is multifactorial disease.…”
mentioning
confidence: 99%
“…Bovine pneumonic pasteurellosis (BPP) caused by Mannheimia (Pasteurella) haemolytica serotype 1 remains a major economic problem for the beef and dairy cattle industries in North America and Western Europe (2,10,14,47). The leukotoxin (LktA) produced by this bacterium is the primary virulence factor that contributes to the pathogenesis of the fibrinonecrotizing pleuropneumonia and death characteristic of this disease (7,8,43,44).…”
mentioning
confidence: 99%